Adjustment status of warfare Veterans with one eye blindness in Zanjan, and it's relationship with personal variables - Mansor Ghafouri Fard; Mitra Payami Bousaria; Ali reza Heyadari Some A (Zanjan University of Medical Sciences and Health Services, 2012)
Background and Aim: War is an unpleasant event imposes for peoples and that causes physical and psychological disorders. One of these complications is blindness. Whereas the blindness may affect the adjustment state of warfare veterans and also the psychological effects of blindness was not studied. So this study was performed to detect the adjustment status among warfare Veterans with one eye blindness in Zanjan city, 2011.   Materials and Methods: This study is a crosssectional analytical descriptive study which 45 warfare veterans of zanjan city participated in the study according to census. Data was gathered using Bell Adjustment inventory . We used SPSS ver.16 and ANOVA test for statistical analysis.   Results: 45 warfare veterans of zanjan city with mean age of 48 ± 7 years participated in the study. The results showed that 66/7% of samples had moderate home adjustment. Only 11/1% had good home adjustment. Regarding to the health adjustment, most portions of samples (66/7%) had fair adjustment. Pearson correlation showed a meaningful relation between health adjustment and age of veterans (p=0/041, r=-0/30). Pared t-test showed meaningful differences between means of home and health adjustment scores. There was a meaningful difference between social adjustment and age category (p=0/016). But there were no differences in the mean of home and health adjustment scores according to age, marriage status, education, exercise, income, percentage of veterans and reason of hurt ( p>0/05).   Conclusion : In this study, a lot of veterans had not a good adjustment. So it is expected from authorities of our country to pay a lot of attention to the psychological status of veterans and holds the educational sessions about life skills and active participating in social fields to promote the physical and psychological health of veterans.